Mental toughness attributes in Judo: perceptions of athletes - Silva, Virgílio; Dias, Cláudia; Corte-Real, Nuno; Manuel Fonseca, António (Cuadernos de Psicología del Deporte, 2018)
Perceptions of mental toughness attributes were explored among Judo competitors. Twelve Portuguese judokas from different levels of achievement underwent a semi-structured interview, based on Personal Construct Psychology “sociality” and “dichotomy” corollaries (Kelly, 1991). Properties and dimensions of each conceptual category arose from the data among the verbatim transcribed interviews. Inductive content analysis revealed 22 attributes that composed mental toughness in competitive Judo. Emotional regulation, resilience, self-confidence, attention regulation, self-motivation and optimism were reported by all subjects of the sample. In relation to previous single-sport researches that explored mental toughness attributes, our results supported the existence of large conceptual similarities across sports, despite subtle differences in Judo discussed in reference to optimism, self-improvement, pragmatism and self-presentation regulation. Self-esteem and adaptability emerged as a novelty in the sport’s mental toughness literature. Combativity was suggested to be the only mental toughness attribute rather peculiar to Judo.